Optimizing Resource Acquisition Decisions by Stochastic Programming - Bienstock, Daniel; Shapiro, Jeremy F. (Management Science, 1988)
This paper reports on the application of stochastic programming with recourse to strategic planning decisions regarding resource acquisition. A resource directed decomposition method, which simultaneously exploits stochastic programming and mixed integer programming model structures, is proposed. Computational experience with the method applied to fuel contract and plant construction decisions faced by an electric utility is presented.